Determinants of IPO Underpricing in Indonesia: Liquidity, Profitability and Underwriter Reputation - Rosa Nur Haliza Safitri (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Initial public offerings often experience underpricing, where the offering price is lower than the first-day closing price, reflecting investor demand and market dynamics in Indonesia. This study aims to analyze the influence of liquidity, profitability, leverage, company size, company age, and underwriter reputation on underpricing for companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research employed purposive sampling to select 224 companies meeting the criteria of underpricing, complete annual reports, and positive profits, with 193 companies included in the final analysis after data cleaning. Multiple linear regression was used to examine the relationships, supported by descriptive statistics and classical assumption tests. The findings reveal that only profitability, measured by return on assets, significantly influences underpricing, indicating that investors prioritize financial performance. Liquidity, leverage, company size, company age, and underwriter reputation show no significant individual effects, though they collectively impact underpricing. This suggests that companies with strong profitability may experience higher underpricing due to increased investor demand, offering insights for issuers to optimize financial performance before initial public offerings and for investors to focus on profitability metrics.